Good Intentions are Not Good Relations: Grounding the Terms of Debt and Redress at Land Grab Universities - Alberta Palmer, Meredith (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
As part of a violent project US imperial expansion into Indigenous lands, the 1862 Morrill Act endowed and continues to accrue lasting benefits for Land Grant/Grab Universities (LGUs). The last three years have seen a surge in nationwide attention and mobilization for redress and calculations of debts owed to Indigenous Peoples for the land dealings of the 52 original LGUs. This article intervenes in the LGU question in two parts. First, I demonstrate culpability of LGUs by illustrating how the Morrill Act was part of a set of US imperial policies that expanded jurisdiction into Indigenous territories through violent and imperial acts of dispossession which are maintained today. Second, I argue that any terms of debt and redress for this dispossession must be framed within Indigenous and Indigenous feminist analytics of land and territory. Restitution cannot occur on the same terms as dispossession and instead must be built through repairing and maintaining good relations within specific Indigenous protocols. These interventions inform my concluding analysis of university administrations’ responses to growing advocacy around LGUs, with a focus on Cornell University where I am situated as a researcher.